The construction of a transnational Lusophone media space: A historiographic analysis. (1st October 2016) - Davis, Stuart; Straubhaar, Joseph; Ferin Cunha, Isabel
ABSTRACT: This piece examines the historical construction of a Lusophone cultural-linguistic media space and market that spans portions of Europe, Africa, and South America. Beginning with the Portuguese colonization of Brazil and Lusophone Africa in the 17th century and continuing to the contemporary moment, our discussion examines how a combination of political, ideological, and economic patterns created linkages between Portugal, Brazil, and Portuguese-speaking colonies in Africa (namely Angola, Cape Verde, and Mozambique). After examining how Brazil grew to become the dominant cultural producer in this transnational matrix (most explicitly expressed through the massive exports of telenovelas and music since the late 1970s), we examine how other countries are beginning to carve out distinctive national niches, including the contemporary music scene in Cape Verde and the rise of domestically produced telenovelas in Portugal and Angola that are increasing in circulation in the contemporary transnational Lusophone media space.